The Impact of Dizziness on the Quality of Life of 235 Individuals who Completed Vestibular Testing in Brazil - Burle,Najlla Lopes de Oliveira (2016)
Introduction In Vestibular Testing (VT), caloric tests allow evaluation of unilateral weakness (UW) and directional preponderance (DP), where different criteria of normality are adopted in Brazil and worldwide. The Brazilian version of the Dizziness Handicap Inventory (Brazilian DHI) evaluates the impact of dizziness on the quality of life of an individual. Objectives The objective of this research is to evaluate the impact of dizziness on the quality of life of patients undergoing VT, and to relate these findings to the results obtained according to national and international criteria. Methods Cross-sectional analytic study of 235 patients referred for VT in two hospitals. The authors performed the Brazilian DHI, history, static, and dynamic balance tests, positional nystagmus, and the Dix-Hallpike maneuver, as well as vectoelectronystagmography. Subjects were divided into three groups according to UW and DP values. Descriptive statistics and comparisons between groups were performed, considering a significance level of 5% in all analyses. Results Patients groups had 20.9% men, and 79.1% women. There was no significant difference between groups for the scores obtained in the Brazilian DHI. There was, however, a statistically significant difference in the redistribution of individuals according to the UWand DP values. Conclusion There was no relationship between VT results and the impact of dizziness in the quality of life. A review of normal values for UW and DP adopted in Brazil is suggested, as well as the application of the Brazilian DHI as an additional tool to evaluate the impact of dizziness on quality of life in all patients undergoing VT.